Mediating effect of teachers’ job satisfaction on principals’ distributed leadership and teachers’ organizational commitment at international schools in Kuala Lumpur / Vicneswary Muthiah - Vicneswary , Muthiah (2020)
The concept of distributed leadership has gained more interest in the educational sector and promoted positive development of school leadership in international schools. Thus, this study investigated the role of principals’ distributed leadership in international schools in Kuala Lumpur, Malaysia in enhancing teachers’ organizational commitment through the mediation of teachers’ job satisfaction. Based on a descriptive and quantitative research design, this study has employed survey method with the distribution of questionnaire from three adapted measurement scales: The Distributed Leadership Inventory, the Teacher Job Satisfaction Scale and the Organizational Commitment Questionnaire. Rasch measurement was used to ensure that the scales had acceptable measures of reliability and validity. Cronbach’s alpha values exceeded 0.70, person reliability and item reliability were above 0.80, item separation and person separation exceeded 2.0 for each of the scales. Using stratified random sampling, 200 respondents among teachers were selected from ten international schools. The structural equation modeling based on a partial least square was utilized in this study to examine the direct and indirect relationships among the variables. Data were statistically analyzed using IBM SPSS Ver. 23.0 and SmartPLS Ver. 3.2.8. Findings showed that the principals’ distributed leadership has a positive and significant relationships with teachers’ job satisfaction and teachers’ organizational commitment. The teachers’ job satisfaction and teachers’ organizational commitment relationship was also positive and significant. The dimensions of principals’ distributed leadership, namely: leadership function quality and distribution, cooperation within the leadership team and teacher decision-making participation were positively and significantly related to teachers’ organizational commitment but not the dimension of supervision quality and distribution. It was found that teachers’ job satisfaction plays the role of a mediator in the relationships of principals’ distributed leadership and teachers’ organizational commitment. Findings showed that the relationships of two dimensions of distributed leadership (cooperation within the leadership team and teacher decision-making participation) with teachers’ organizational commitment were mediated but for another two dimensions (leadership function quality and distribution and supervision quality and distribution) were not mediated by teachers’ job satisfaction. Overall, the predictive accuracy and relevancy of the research model could explain the principals’ distributed leadership’s effect on job satisfaction of the teachers (R2 = 0.417, Q2 = 0.234, f2 = 0.694) and on teachers’ organizational commitment (R2 = 0.786, Q2 = 0.481; f2 = 1.583). These findings contributed significantly mainly to provide evidence empirically on the importance of principals’ distributed leadership to improve teachers’ satisfaction and commitment. This study provides a good foundation to conduct more studies on principals’ distributed leadership and its outcome in terms of job satisfaction and organizational commitment of the teachers with a broader population coverage. The findings call for an enriching of the research model with the inclusion of other educational outcomes such as student and school performance. Conclusively, this study advocates the effective and efficient practices of principals’ distributed leadership to ensure high job satisfaction and organizational commitment level among teachers so as to ensure high quality education services in international schools in Malaysia.